Overexpression of microRNAs enhances recombinant protein production in Chinese hamster ovary cells. Issue 9 (23rd June 2014) - Loh, Wan Ping; Loo, Bernard; Zhou, Lihan; Zhang, Peiqing; Lee, Dong‐Yup; Yang, Yuansheng; Lam, Kong Peng
Abstract MicroRNAs (miRNAs) are short, non‐coding RNAs that can negatively regulate expression of multiple genes at post‐transcriptional levels. Using miRNAs to target multiple genes and pathways is a promising cell‐engineering strategy to increase recombinant protein production in mammalian cells. Here, we identified miRs‐17, ‐19b, ‐20a, and ‐92a to be differentially expressed between high‐ and low‐ monoclonal antibody‐producing Chinese hamster ovary (CHO) cell clones using next‐generation sequencing and quantitative real‐time PCR. These miRNAs were stably overexpressed individually and in combination in a high‐producing clone to assess their effects on CHO cell growth, recombinant protein productivity and product quality. Stably transfected pools demonstrated 24–34% increases in specific productivity (qP) and 21–31% increases in titer relative to the parental clone, without significant alterations in proliferation rates. The highest protein‐producing clones isolated from these pools exhibited 130–140% increases in qP and titer compared to the parental clone, without major changes in product aggregation and N‐glycosylation profile. From our clonal data, correlations between enhanced qP/titer and increased levels of miRs‐17, ‐19b, and ‐92a were observed. Our results demonstrate the potential of miRs‐17, ‐19b, and ‐92a as cell‐engineering targets to increase recombinant protein production in mammalian cells.